Maximizing Returns on Human Capital Investment in Mongolia : Policy Note for Mongolia - World Bank (World Bank, Washington, DC, 2020)
Human capital is a crucial factor of economic development. As stated in Mongolia’s vision 2050, the country has so far relied heavily on its natural resources for development. It puts the human development in the center of its strategy, envisioning that children and youth will be educated at world-class standards, adopt active lifestyle, benefit from life-sustaining social protection services, science, and technology. Only by investing in human capital and innovation can Mongolia achieve more sustainable and stable economic growth. This policy note presents key policy options for the new government of Mongolia to protect and maximize the human potential and its contribution to equitable growth.